(3eNJUQ GdQhVI GdbOGejIs - (3fLe GdOjf SdjeGf Hf YHO Gdbhi GdWhai GdMfHdis; (3G MeO Hf GdMSjf Hf bOGeg GdMfHdjs
(3ChdgG (B:s
(3bGd GdTjN fLe GdOjf SdjeGf Hf YHO Gdbhi GdWhai afbhd hHGddg GdJhajb CUhd Gdabg COdJg adfJcde YdjgG CUdkG CUdkG HYO PcQ ebOeI JTJed Ydi aUhd GdChd ai JYQja CUhd Gdabg hgh eQcH ef s
(3BNQgG (B:s
(3hJaGUjd GdJQLjM cKjQI aGdVGHW ajg Cfg eJi EbJQf HCMO GdWQajf CeQ fbdi hEUWdGMi YGe Ch NGU Ch bQjfI YbdjI Ch daXjI hhLg GdQLMGf ai CcKQ gPg GdJQLjMGJ Hjf adgPG CgedfG PcQg ENJUGQkG hGddg CYde s
(3GdfSNI HgG MhGTs
(3YdjgG ELGRI HNW CMeO Hf GdMSf Hf bOGeI GdMfHdi SfI (B742(3g` dCHi GdaJM fUQ Gddg Hf TgGH GdOjf CMeO Hf CHj GdaJM GdYSbdGfi GdMfHdis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3GdJUha hGdBOGH GdTQYjIs